KEMAMPUAN INOVASI PELAYANAN PEGAWAI - Wiyata Ariefebriana; Johanes Basuki; Meyzi Heriyanto (Universitas Riau, 2018)
Ability of Employee Service Innovation. This study aims to analyze theperformance and tasks at the Bureau of Organization Office of the Regional Secretariat of RiauProvince. The method used is descriptive qualitative. primary data obtained from interviewdani. Secondary data is obtained from collecting data with documents. Data analysis usedgenetic data, data reduction, data presentation, and deduction of conclusions. The results ofresearch that shows optimal performance This is evident from the factors of leadership,mastery of technology in the mastery of information technology and imperfect governmentprograms move in its use.